EFEK PEMBERIAN REBUSAN KULIT JENGKOL (ARCHIDENDRON PAUCIFLORUM) SEBAGAI ANTIDIABETIK TERHADAP KADAR MALONDIALDEHYDE (MDA) TIKUS PUTIH YANG DIINDUKSI STREPTOZOTOCIN - RADEN FEBRIAN DWI CAHYO EDI PRABOWO; FANI ADE IRMA (JURNAL ILMIAH SIMANTEK, 2020)
Diabetes mellitus is a metabolic disorder with many symptoms where an increase in oxidative stress plays an important rolein the pathogenesis of disease and can lead to the formation of reactive oxygen species (ROS) so as to increase freeradicals. lipids will eventually produce aldehydes, one of which is malondialdehyde (MDA) which is commonly used as abiological biomarker of lipid peroxidation and describes the degree of oxidative stress. This study aimed to determine theeffect of giving jengkol cooking water on malondialdehyde (MDA) levels in blood plasma of streptozotocin-induced malewistar rats (Rattus novergicus L.) white rats. True experimental posttest only control group design. Significant results ofplasma malondialdehyde (MDA) levels between the control and treatment groups were p> 0.05. The administration ofjengkol decoction with 80% concentration at a dose of 40 mg / KgBB / rat / day for 14 days affected the decrease in plasmaMDA previously streptozotocin induced.